Antenna subset selection for V-BLAST systems based on permutation and QR decomposition - LI Li1; ZHU Guang-xi1; XIAO Xiao1; LIU Jian1 (Tongxin xuebao)
A novel antenna subset selection in V-BLAST systems with ordered successive interference cancellation （OSIC） detection was presented. With an eye to the impacts of ordering and cancellation, by use of permutation and QR decom-position, a terse antenna subset selection mathematic expression with reasonable complexity for V-BLAST was put for-ward. Simulation results show that the proposed selection criterion achieves near-optimal outage capacity and outper-forms several existing ones in performance.